2002
DOI: 10.1046/j.1365-2222.2002.01430.x
|View full text |Cite
|
Sign up to set email alerts
|

An oral introduction of intestinal bacteria prevents the development of a long‐term Th2‐skewed immunological memory induced by neonatal antibiotic treatment in mice

Abstract: These results suggest that adequate probiotic intervention after antibiotic treatment may improve the intestinal ecosystem, and thereby prevent the Th2-shifted immunity induced by neonatal antibiotic use. In addition, the difference of genetic backgrounds also contributes to such an antibiotic-induced Th2-skewed response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 20 publications
1
71
1
2
Order By: Relevance
“…30). In addition to CpG ODN, studies in both experimental models (31) and clinical trials (32) have shown that certain types of bacteria, notably Lactobacilli, can act as immunomodulatory "probiotics" to ameliorate allergic inflammation. Whether this is related to differential signaling by TLRs, or groups of TLRs, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…30). In addition to CpG ODN, studies in both experimental models (31) and clinical trials (32) have shown that certain types of bacteria, notably Lactobacilli, can act as immunomodulatory "probiotics" to ameliorate allergic inflammation. Whether this is related to differential signaling by TLRs, or groups of TLRs, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…vent the Th2 shifted immune responses induced by neonatal antibiotic use. 1) As for the systemic immune response, total IgG1 and IgG2a concentrations in the serum were measured for comparison with the mucosal immune response. We have shown that LS supplementation can suppress serum IgG1 levels, as a Th2 type reaction (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the mucosal membrane in the intestinal tract act, as an important front line defense barrier, plays important roles. Probiotics 1) is defined as microbial food supplements that beneficially affect the host by improving its intestinal microbial balance. Prebiotics, 2) such as dietary indigestible oligosaccharides, also beneficially affect the host by selectively stimulating the growth and or activity of one or a limited number of health promoting indigenous flora.…”
mentioning
confidence: 99%
“…Given the wide spread use of antibiotics in the outpatient pediatric population, it is important to discuss some of the association between childhood antibiotic exposure and alterations of the gut microbiome. Antibiotics can induce an atopy-prone state by promoting an increase in the Th2 phenotype [37,38]. Even particular antibiotics show certain associations in relation to the gut microbiome, such as metronidazole, which decreases mucin secretion and intestinal barrier integrity by reducing the expression of the MUC2 gene [39].…”
Section: The Role Of the Gut Microbiome In Immune System Developmentmentioning
confidence: 99%